The HPA – Immune Axis and the Immunomodulatory Actions of Glucocorticoids in the Brain - Bellavance, Marc-Andre; Rivest, Serge (Frontiers in Immunology, 2014)
In response to physiological and psychogenic stressors, the hypothalamic-pituitary adrenal (HPA) axis orchestrates the systemic release of glucocorticoids (GCs). By virtue of nearly ubiquitous expression of the GC receptor (GR) and the multifaceted metabolic, cardiovascular, cognitive and immunologic functions of GCs, this system plays an essential role in the response to stress and restoration of an homeostatic state. GCs act on almost all types of immune cells and were long recognized to perform salient immunosuppressive and anti-inflammatory functions through various genomic and non-genomic mechanisms. These renowned effects of the steroid hormone have been exploited in the clinic for the past 70 years and synthetic GC derivatives are commonly used for the therapy of various allergic, autoimmune, inflammatory and haematological disorders. The role of the HPA axis and GCs in restraining immune responses across the organism is however still debated in light of accumulating evidence suggesting that GCs can also have both permissive and stimulatory effects on the immune system under specific conditions. Such paradoxical actions of GCs are particularly evident in the brain, where substantial data support either a beneficial or detrimental role of the steroid hormone. In this review, we examine the roles of GCs on the innate immune system with a particular focus on the CNS compartment. We also dissect the numerous molecular mechanisms through which GCs exert their effects and discuss the various parameters influencing the paradoxical immunomodulatory functions of GCs in the brain.